An Ethnography of Time Perception in Pesantren Culture: A Study of Pondok Pesantren Bahrul Ulum Al-Hamid - Abdurrohman Sholeh; Panji Muhammad Nur Sholih (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2026)
This study examines how time is perceived and negotiated within pesantren culture, focusing on the routine lateness of the kiai in activities he leads compared to the strict time discipline enforced upon santri, at Pondok Pesantren Bahrul Ulum Al-Hamid, Gondanglegi. Using an ethnographic-phenomenological design, data were collected through semi-structured interviews with nine santri, three ustadz/ustadzah, and one kiai. Analysis combined the emic framework of adab thalabul ilmi with the etic lens of hidden transcript theory. Findings show that the kiai's lateness is normalized through in-group language and productive waiting practices, sustained by a stark asymmetry in sanctions between santri and kiai, and produces differentiated voice among santri: some accept the culture as a path to barakah, while others express discontent only in guarded, off-stage talk rather than openly. Tenure alone does not predict this stance; individual disposition matters as much as length of stay. Pengurus and junior ustadz act as buffering actors absorbing tension between kiai and santri. The novelty of this study lies in showing that the durability of the 'jam karet kiai' culture rests less on the absence of grievance than on layered mechanisms -- linguistic, theological, and structural -- that keep grievance from surfacing, contributing to the study of informal power relations in religious institutions.